Evaluation of the Relationship Between Metformin Use and Kidney Function in Geriatric Patients Diagnosed with Type 2 Diabetes Mellitus in the Inpatient Ward of Level II Hospital Prof. Dr. J. A. Latumeten Ambon - Maryanti Tuharea; Diana Laila Ramatillah (Eduvest - Journal of Universal Studies, 2025)
Metformin is a first-line therapy for type 2 diabetes mellitus (Type 2 DM), but its primary excretion through the kidneys raises concerns about the risk of nephrotoxicity, particularly in geriatric patients. This study aims to assess the relationship between metformin use and renal function in geriatric patients with Type 2 DM at Prof. Dr. J. A. Latumeten Ambon Level II Hospital. This study used a retrospective and prospective observational design of 150 geriatric patients receiving metformin. Data were collected through medical records and questionnaires. Kidney function parameters are assessed through GFR values and creatinine levels. The results of the study showed that the majority of respondents were aged 66–74 years (88.7%), with a prevalence of metformin use of 100%. No significant association was found between the duration of metformin use and a drastic decline in kidney function (the average creatinine value remained < 1.3 mg/dL). However, comorbidities and age were found to be factors that affect kidney function more significantly. Metformin is relatively safe to use in geriatric patients with close monitoring of renal function. The decline in kidney function is more influenced by age factors and comorbidities than by the use of metformin itself.